Monitorização da complacência intracraniana em pacientes com COVID-19: estudo observacional multicêntrico - Silveira, Ana Flávia (Universidade Federal de São Carlos, 2022)
COVID-19 pandemic overloaded health system around the world due to high number of hospitalized patients. In many cases the disease severity can demand intensive unit care orothraqueal intubation included to maintain life. Neurological symptoms were reported in subjects with COVID-19, however, the physiopathology about how coronavírus infects the Nervous Central System (NCS) is not well established. Endothelium dysfunction is one pathway that can explain changes in Cerebrovascular Hemodynamic (CVH). The compensatory capacity to maintain intracranial volumes as result from pressure alteration is knowledge as Intracranial Compliance (ICC) and can help to understand the COVID-19 action on NCS. Thus the aim of this study is to characterize ICC in patients intubated and non-intubated with COVID-19. Methods: This is a multicenter observational study which enrolled intubated and non-intubated patients with COVID-19 within 14 days onset and until 72h from hospital admission. Two control groups were also monitored (one control under Orothraqueal Intubation [OTI] and other with healthy subjects). ICC monitoring was performed by Brain4Care’s non-invasive sensor, positioned on temporal bone. ICP wave morphology was evaluated using its 3 peaks: P1 (systolic pulse); P2 (vascular pulse) and P3 (aortic valve closure). In physiological conditions this relation is characterized by P1 > P2 > P3. The ICC monitoring occured once during 60 minutes. and we used P2/P1 and Time To Peak (TTP) ratio as outcome. An independent T test was used to compare COVID-19 OTI with COVID-19 non-OTI, COVID-19 OTI with control OTI and, COVID-19 non-OTI with healthy control group. Results: 78 subjects were enrolled in this study and divided in 4 groups: 1) COVID-19 OTI (n = 15); 2) COVID-19 non-OTI (n = 24); 3) OTI control (n = 15) and 4) healthy control (n = 24). The COVID-19 OTI showed to have a bigger average of P2/P1 ratio when it was compared to COVID-19 non-OTI and TTP ratio than OTI control group. Both non-intubated group had no difference between them. Conclusion: Individuals with COVID-19 under invasive mechanical ventilation appears to have an ICC impairment.
Intracranial compliance in patients with COVID-19: a multicenter prospective study
Keywords: Hemodinâmica cerebrovascular; Pressão intracraniana; Complacência intracraniana; Coronavírus 2019; Cerebrovascular hemodynamic; Intracranial pressure; Intracranial compliance; Coronavírus 2019; SARS-CoV-2; COVID-19; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL